Co-occurring increased phosphatase activity and labile P depletion in the rhizosphere of Lupinus angustifolius assessed with a novel, combined 2D-imaging approach. (February 2021) - Hummel, Christina; Boitt, Gustavo; Santner, Jakob; Lehto, Niklas J.; Condron, Leo; Wenzel, Walter W.
Abstract: Innovative non-destructive 2D imaging methods such as zymography and diffusive gradients in thin films (DGT) have been developed recently to assess the distribution of phosphatase activity and labile solutes at the root-soil interface. We report on the first combination of these techniques for the spatial distribution and potential interaction of labile phosphorus (P) and associated acid phosphatase activity in the rhizosphere of blue lupin ( Lupinus angustifolius ) in two contrasting soils ('Sand' and 'Loam'). Zymography, based on 4-methylumbelliferylphosphate (MU-P) for acid phosphatase activity mapping, and DGT gels capable of binding labile P were deployed to individual root axes to visualise P mobilisation and depletion in the rhizosphere of blue lupin grown in rhizotrons in glasshouse conditions for 45 days. Acid phosphatase activity was evidently higher in the rhizosphere and co-occurred with P-depletion zones around the roots in both soils. Lateral root profiles showed that elevated acid phosphatase activity as well as P-depletion extended up to 2 mm from the root centre into the rhizosphere. Despite larger total and organic P pools in the Loam, P was less plant available (DGT labile P) than in the Sand. However, phosphatase activities in the rhizosphere and plant P contents were similar in both soils. These results indicate that enzyme-catalysed hydrolysis of organic P was limited in the Loam, due to low P availability, hence explaining similar P contents in lupins from both soils. P did not accumulate in labile pools in the rhizosphere indicating that P supply via phosphatase could not compensate the plants demand for P resulting in P depletion zones. While our work demonstrates the applicability of combined zymography and DGT deployments to study rhizosphere processes at microscale, we also discuss limitations and perspectives of this approach. Graphical abstract: Image 1 Highlights: The co-occurrence of phosphatase activity and P depletion along roots was studied. We combined phosphatase activity and labile P imaging for the first time. We observed increased phosphatase activity along roots compared to bulk soil. P depletion co-occurred with increased phosphatase activity at root locations. We found no labile phosphorus accumulation in the rhizosphere.